2009
DOI: 10.1002/er.1628
|View full text |Cite
|
Sign up to set email alerts
|

Energy and exergy analysis of an experimental single-stage heat transformer operating with the water/lithium bromide mixture

Abstract: SUMMARYThe first and second law of thermodynamics have been used to analyze the performance of an experimental single-stage heat transformer operating with the water/lithium bromide mixture. Enthalpy coefficients of performance (COP), external coefficients of performance (COP EXT ), exergy coefficient of performance (ECOP), exergy destruction or irreversibility in the system and components (I) and the improvement potential (Pot) have been calculated against the gross temperature lift and the main operating tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Although the main aim of this study is to find out global optimum value of the cycle but also some of our studies have been carried out, in order to understand the variation of aim functions of the system with different working temperatures (T 3, T 5, T 8 , and T 12) , different solution heat exchanger effectiveness and isentropic efficiency of compressors. LiBr is a salt, and it has a crystalline structure in its solid state.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the main aim of this study is to find out global optimum value of the cycle but also some of our studies have been carried out, in order to understand the variation of aim functions of the system with different working temperatures (T 3, T 5, T 8 , and T 12) , different solution heat exchanger effectiveness and isentropic efficiency of compressors. LiBr is a salt, and it has a crystalline structure in its solid state.…”
Section: Resultsmentioning
confidence: 99%
“…Related costs in Eq. (12) can be written as [17]: For the base case, the cost flow rates [C ($ h À1 )] and cost per exergy unit [c ($ GJ À1 )] for each stream of the system that are presented in Table 3.…”
Section: Thermodynamic Analyses Of the (Libr/h 2 O-r134a) Compressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Siqueiros and Romero [17] demonstrated that by raising the evaporator temperature by 1 1C the COP of the cycle can be increased by up to 78%, while a 2 1C augmentation in the heat source temperature can result in an increase in the COP of up to 121%. To the author's best knowledge, the only SSHT publication to contradict any of the above trends was presented by Rivera et al [18], who found that their experimental COP decreased with an increase in the evaporator temperature. No analysis was provided regarding possible reasons for this deviation.…”
Section: Ssht Parametric Studiesmentioning
confidence: 92%
“…Rivera et al [18] demonstrated experimentally that the absorber accounts for half of the total irreversibility followed by the condenser and the generator whose exergetic efficiencies are shown to be similar. Rivera et al [24] similarly attributed 30% of the irreversibility to the absorber, followed by the condenser.…”
Section: Ssht Parametric Studiesmentioning
confidence: 94%